How The One-Stop Services from Mobile Applications Aligned with Customers' Contemporary Purchasing Behavior: A Study on Grab’s Brand Recognition Among Customers - See Pei Joe; Qiu Lin Hui; Rashidah Nabila binti Zakaria Ansori; Sheron Tan Ming Er; Rinku Ojha; Aniket Kabade; Harini Rajan (AIBPM Publisher, 2024)
The ride-hailing app Grab has now grown into a multinational transportation company headquartered in Singapore with offices in eight Southeast Asian countries. Since its founding in 2012, the company has expanded beyond its core business of ride-hailing services to transportation, delivery, finance and insurance, enterprise, and more, all integrated into a cloud-based system. This study is being conducted to find out how Grab, with its core function as a ride-hailing application, fits into customers' contemporary purchasing behavior and how the company has developed a strong brand recognition among its customers. Five influential aspects were evaluated: the super app, flat rate fees, short waiting times, reliability, and environmental friendliness. A total of 201 Grab users participated in an online survey, and IBM SPSS was used to analyse the results. The results showed that factors such as super app, flat rate fees, environmental friendliness, and reliability are positively related to customers purchasing behavior. Short waiting times, though, had no significant impact on customers' purchasing behavior. This survey gives Grab important information on how customers view the company, which helps them boost brand awareness.